Eksistensi Budaya Lokal sebagai Model Pengembangan Dakwah: Pendekatan Sosiologis - Moh. Anif Arifani (Faculty of Da'wah and Communication, UIN Sunan Gunung Djati, Bandung, 2008)
The culture constitute one of entities that can’t diabaikan in da’wah. When da’wah implemented, the values of Islamic doctrin as message of da’wah will touch reality of local society local culture. Its concequence is not simple, pertemuan dua kebudayaan can create benturan-benturan or otherwise create accommodative. For reaching (menggapai) complited da’wah in meeting context with the culture, da’I has to own wisdom. Its urgently skill of da’wah based local culture to developed.